2017
DOI: 10.5194/os-2017-8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling of sediment transport and morphological evolution under the combined action of waves and currents

Abstract: Abstract. Coastal defence structures are often constructed to prevent beach erosion. However, poorly designed structures may cause serious erosion problems in the downdrift direction. Morphological models are useful tools to predict such impacts and assess the efficiency of defence structures for different scenarios. Nevertheless, morphological modelling is still a topic under intense research effort. The processes simulated by a morphological model depend on model complexity. For instance, undertow currents a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…where V represents the control volume, v H =(u,v) the horizontal velocity vector, v=(u,v,w) the velocity vector, n the normal vector to the bounding surface A, n H the normal vector related to the horizontal plane, υ T the turbulent viscosity, r the water density, p = g Z h z rdz +P atm the water presure, g is gravitational acceleration, P atm the atmospheric pressure, h the water level, W the earth rotation vector, and F is external forces, which include the wave induced force (gradient of radiation stress) computed by the wave model. The wave induced force was considered in the model MOHID in different systems (Malhadas et al, 2009;Malhadas et al, 2010;Delpey et al, 2014;Franz et al, 2017).…”
Section: The Model Description and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…where V represents the control volume, v H =(u,v) the horizontal velocity vector, v=(u,v,w) the velocity vector, n the normal vector to the bounding surface A, n H the normal vector related to the horizontal plane, υ T the turbulent viscosity, r the water density, p = g Z h z rdz +P atm the water presure, g is gravitational acceleration, P atm the atmospheric pressure, h the water level, W the earth rotation vector, and F is external forces, which include the wave induced force (gradient of radiation stress) computed by the wave model. The wave induced force was considered in the model MOHID in different systems (Malhadas et al, 2009;Malhadas et al, 2010;Delpey et al, 2014;Franz et al, 2017).…”
Section: The Model Description and Setupmentioning
confidence: 99%
“…Filling The gap, the present work is focused on the effects of waves on hydrodynamics, processes such as stratification, circulation, and salt wedge dynamics are evaluated in the MRE. Field data and the coupling of the 3D MOHID finite volume model (Neves, 1985;Leitão, 2003;Franz et al, 2017), with the SWAN spectral wave model (Booij et al, 1999), previously calibrated and validated, were used. The low freshwater discharge seasons of 2018 and 2020 were taken as case studies, simulating current-only conditions (tidal and river), and comparing the results with simulations that include also the effects of waves on hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is indicated that a lot of deposits might accumulate there, which in turn can change the morphology of the coastal zone. Sea currents and waves leading to the coast can contribute to the morphological changes in the coastal zone as in the form of sediments [53]. Specifically, Taniguchi et al [54] explain that residual currents affect sediment deposition on the coast.…”
Section: Characteristics Of Soc In the Flores Seamentioning
confidence: 99%